Preparation method of silicon-carbon negative electrode material
By utilizing the silicon waste generated in the production process of lithium-ion batteries, the silicon negative electrode material is prepared and carbon coated, the problems of poor conductivity and volume expansion of silicon negative electrode materials are solved, the circulation and safety performance are improved, and the utilization and cost savings are achieved.
Patent Information
- Application Number
- CN202411949432.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Due to poor conductivity and volume expansion problems of existing lithium-ion battery negative electrode materials, silicon, leads to structural powdering and electrode collapse, reducing circulation and safety performance.
The waste silicon produced by linear cutting during the production process of semiconductor-grade silicon single-crystal chips or solar-grade silicon multi-crystal chips is used to prepare high-performance silicon-carbon negative electrode materials through removal of impurities, preparation of porous nano-silicon materials and carbon coating.
The conductivity and cyclic performance of silicon negative electrode materials are improved, volume expansion is reduced, safety performance is enhanced, and waste utilization is realized, which significantly saves costs.
Smart Images

Figure CN119764390A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery materials, and in particular relates to a method for preparing a low-cost and high-stability negative electrode material for lithium-ion batteries by using silicon waste from the photovoltaic industry. Background Art
[0002] From the perspective of the development of negative electrode materials for lithium-ion batteries, the theoretical specific capacity of graphite is 372mAh / g. In current commercial power batteries, the specific capacity of graphite negative electrodes is 340-370mAh / g, which has reached its limit and is difficult to improve further. The specific capacity of single Si is as high as 4200mAh / g, which is ten times the theoretical specific capacity of graphite. It is an important development direction for negative electrode materials for lithium-ion batteries at home and abroad. However, silicon negative electrode materials have poor conductivity, and their volume expands greatly during discharge, and their volume shrinks during charging, which leads to serious problems such as pulverization and degradation of the silicon negative electrode structure and electrode collapse, greatly reducing its cycle performance and safety performance. This has become the main challenge facing current research and applications.
[0003] In order to solve the problem of large volume expansion of silicon negative electrode materials during the process of lithium insertion and extraction, researchers mainly solve it from two aspects: silicon nano-sizing and special structure (core-shell, 3D porous). ① In the prior art, silicon nano-sizing refers to the main use of ball milling, spray granulation and other methods, which are relatively costly, and the silicon negative electrode structure will still be pulverized after long-term charging and discharging, and the cycle life cannot be guaranteed; ② In the prior art, special structures such as core-shell and 3D porous often appear alone in a silicon-carbon negative electrode, and the preparation process is complicated, and it does not involve the simultaneous appearance of core-shell and 3D porous structures in a silicon-carbon negative electrode material; ③ In the prior art, the preparation of silicon-carbon negative electrode materials does not involve using carbon network as a conductive carrier to improve the conductivity of silicon-carbon negative electrode; ④ In the prior art, silicon-carbon negative electrode materials do not involve the simultaneous use of nano-sizing, 3D porous, core-shell structure and carbon network carrier to alleviate the volume expansion of silicon negative electrode during charging and discharging. Invention content
[0004] In view of this, the present invention aims to propose a method for preparing a silicon-carbon negative electrode material to solve the problem that pure silicon is not conductive.
[0005] To achieve the above object, the technical solution created by the present invention is implemented as follows:
[0006] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0007] S1. Remove impurities from waste silicon produced by wire cutting during the production of semiconductor-grade silicon single wafers or solar-grade silicon multi-wafers;
[0008] S2, treating the silicon waste after removing impurities to obtain porous nano-silicon material;
[0009] S3. Reacting the obtained porous nano-silicon material with a carbon source to obtain a silicon-carbon composite material anchored on the carbon surface.
[0010] Furthermore, the specific method of S1 is: using acetone and hydrochloric acid solution to stir and clean the waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystals or solar-grade silicon multi-crystals to remove impurities.
[0011] Furthermore, the specific method of S2 is: using hydrofluoric acid and nitric acid solution to corrode the silicon waste after removing impurities to obtain porous nano-silicon material;
[0012] Furthermore, the specific method of S3 is: using magnesium thermal reaction to react the obtained porous nano-silicon material with a carbon source to obtain a silicon-carbon composite material anchored on the carbon surface.
[0013] Furthermore, the semiconductor-grade silicon single crystal wafer or solar-grade silicon multi-crystal wafer has electrical conductivity, and the silicon content in the silicon waste is ≥95%.
[0014] Furthermore, the molar ratio of acetone to hydrochloric acid solution in S1 is 1:1-2, the liquid-to-solid ratio is 10-15 mL:1 g, and the stirring time is ≥30 min.
[0015] Furthermore, the hydrofluoric acid solution in S2 is ≥1 mol / L, and the nitric acid solution is ≥0.5 mol / L, and the order of adding is first adding the hydrofluoric acid solution and then gradually dropping the nitric acid solution, and the molar ratio of the nitric acid to the hydrofluoric acid solution is 1:1-5.
[0016] Furthermore, the corrosion treatment in S2 refers to continuous stirring to make the nanoporous silicon particles become hydrophobic bubbles floating on the surface of the solution. The experiment is stopped when the silicon turns brown and no bubbles are generated. The precipitate containing porous silicon is collected and washed and dried to obtain a porous silicon negative electrode material.
[0017] Furthermore, in the magnesium thermal reaction in S3, the mass ratio of magnesium powder, porous silicon material and carbon source is 1:1-2:2-5, the heat treatment temperature is 700-900°C, the heating rate is 5°C min-1, and the insulation time is 2-7h.
[0018] Furthermore, the carbon source in S3 is carbon nanotubes, graphene or dicyandiamide.
[0019] Compared with the prior art, the method for preparing the silicon-carbon negative electrode material created by the present invention has the following advantages:
[0020] (1) The present invention creates a method for preparing silicon-carbon negative electrode materials, using waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystals or solar-grade silicon multi-crystals as a raw material to prepare high-performance lithium-ion battery negative electrode materials, which can solve the defect of pure silicon being non-conductive, and realize waste utilization, thereby greatly saving costs.
[0021] (2) The present invention creates a method for preparing silicon-carbon negative electrode materials, which reduces the volume expansion of the silicon negative electrode during the process of lithium insertion and removal, and improves the cycle performance and safety performance of the silicon negative electrode during the process of lithium insertion and removal. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments and descriptions of the present invention are used to explain the present invention and do not constitute an improper limitation on the present invention. In the drawings:
[0023] Figure 1 A flow chart of the method for preparing the silicon-carbon negative electrode material according to the embodiment of the present invention;
[0024] Figure 2 This is a particle size distribution diagram of silicon waste after cleaning with acetone and hydrochloric acid solution in Example 1;
[0025] Figure 3 This is a transmission electron microscope photo of the low-cost and high-stability silicon-carbon negative electrode material in Example 1;
[0026] Figure 4 It is the low-cost and highly stable silicon-carbon negative electrode material in Example 1. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0028] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and the like are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, features defined as "first", "second", and the like may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.
[0029] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood by specific circumstances.
[0030] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments.
[0031] A method for preparing a silicon-carbon negative electrode material, such as Figures 1 to 4 As shown, the following steps are included:
[0032] S1. Using acetone and hydrochloric acid solution to stir and clean the waste silicon generated by wire cutting during the production of semiconductor-grade silicon single wafers or solar-grade silicon multi-wafers to remove impurities;
[0033] S2, using hydrofluoric acid and nitric acid solution to corrode the silicon waste after impurities are removed to obtain porous nano-silicon material;
[0034] S3. The obtained porous nano-silicon material is reacted with a carbon source by using a magnesium thermal reaction to obtain a silicon-carbon composite material anchored on a carbon surface.
[0035] This solution uses waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystals or solar-grade silicon multi-crystals as raw material to prepare high-performance lithium-ion battery negative electrode materials, which can solve the defect of pure silicon being non-conductive, and realize waste utilization, greatly saving costs.
[0036] The semiconductor-grade silicon single crystal wafer or solar-grade silicon multi-crystalline wafer described in S1 has a certain conductivity, and the silicon content in the silicon waste is ≥95%.
[0037] The molar ratio of acetone and hydrochloric acid solution described in S1 is 1:1-2, the liquid-to-solid ratio is 10-15 mL:1 g, and the stirring time is ≥30 min.
[0038] The hydrofluoric acid solution described in S2 is ≥1 mol / L, and the nitric acid solution is ≥0.5 mol / L. The order of adding is to first add the hydrofluoric acid solution and then gradually drop the nitric acid solution. The molar ratio of nitric acid to hydrofluoric acid solution is 1:1-5.
[0039] The corrosion treatment described in S2 refers to continuous stirring to make the nanoporous silicon particles become hydrophobic bubbles floating on the surface of the solution. The experiment is stopped when the silicon turns brown and no bubbles are generated, and the precipitate containing porous silicon is collected and washed and dried to obtain a porous silicon negative electrode material.
[0040] In the magnesium thermal reaction described in S3, the mass ratio of magnesium powder, porous silicon material and carbon source is 1:1-2:2-5, the heat treatment temperature is 700-900°C, the heating rate is 5°C min-1, and the insulation time is 2-7h.
[0041] The carbon source described in S3 is an organic carbon source such as carbon nanotubes, graphene or dicyandiamide.
[0042] Example 1
[0043] Step 1: Take 5mL 1mol / L acetone and 10mL 1mol / L hydrochloric acid and add them to 1g of waste silicon produced by wire cutting during the production of semiconductor-grade silicon single wafers or solar-grade silicon multi-wafers. Stir for 40 minutes to clean and remove impurities. The particle size distribution of the cleaned waste silicon is shown in Figure 1 ;
[0044] This step utilizes waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystals or solar-grade silicon multi-crystals as a silicon source, which not only reduces costs, but also such silicon is already in the form of micro-nano-level particles and does not require nano-processing. A mixed solution of acetone and hydrochloric acid removes organic impurities and metallic impurities from waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystals or solar-grade silicon multi-crystals to obtain pure silicon nanoparticles.
[0045] Step 2: First add 4 ml of 0.5 mol / L hydrofluoric acid solution to the above-mentioned cleaned waste silicon, then gradually drop 15 ml of 0.5 mol / L nitric acid solution, and continue stirring to make the nanoporous silicon particles become hydrophobic foam floating on the surface of the solution. When the silicon turns brown and no bubbles are generated, stop the experiment, collect the precipitate containing porous silicon, wash and dry it, and obtain a porous silicon material.
[0046] This step corrodes the silicon nanoparticles into porous silicon materials in a strong acid solution. The ratio and order of addition of the hydrofluoric acid solution and the nitric acid solution are crucial.
[0047] Step 3: Grind and mix 1g magnesium powder, 1g porous silicon material and 2g carbon nanotubes in a mortar. Carry out carbonization treatment in a tube furnace under argon atmosphere, heat to 750℃ at a rate of 5℃min-1, keep warm for 5h and then cool naturally to room temperature. Wash the above product with 1M HCl to remove reaction by-products, rinse with deionized water and ethanol several times, and dry at 80℃ in vacuum for 24h to obtain a low-cost and highly stable silicon-carbon negative electrode material. Transmission electron microscope photos of low-cost and highly stable silicon-carbon negative electrode materials are shown in Figure 2 .
[0048] This step is to carbon-coat the above-mentioned porous nano-silicon material, which can effectively limit the volume expansion of the silicon negative electrode during the process of lithium insertion and extraction, and form a carbon network to improve the conductivity of the material.
[0049] The obtained low-cost and high-stability silicon-carbon negative electrode material was tested, and the test results are shown in Figure 3 After 200 cycles of charge and discharge, the capacity of the negative electrode material was 594 mAh / g and the coulombic efficiency was 98%.
[0050] Example 2
[0051] The preparation method of low-cost and high-stability silicon-carbon negative electrode material is the same as that in Example 1, except that the amount of hydrofluoric acid added in step 2 is 8 ml. The obtained low-cost and high-stability silicon-carbon negative electrode material is tested. After 200 cycles of charge and discharge, the capacity of the negative electrode material is 580 mAh / g and the coulombic efficiency is 97%.
[0052] Example 3
[0053] The method for preparing low-cost and high-stability silicon-carbon negative electrode material is the same as that in Example 1, except that the amount of nitric acid added in step 2 is 4 ml.
[0054] The obtained low-cost and high-stability silicon-carbon negative electrode material was tested. After 200 cycles of charge and discharge, the capacity of the negative electrode material was 550 mAh / g and the coulombic efficiency was 98%.
[0055] Comparative Example 1
[0056] The method for preparing low-cost and high-stability silicon-carbon negative electrode material is the same as that in Example 1, except that 4 ml of 0.5 mol / L hydrofluoric acid solution and 15 ml of 0.5 mol / L nitric acid solution are added simultaneously in step 2.
[0057] The obtained low-cost and high-stability silicon-carbon negative electrode material was tested. After 200 cycles of charge and discharge, the capacity of the negative electrode material was 325 mAh / g and the coulombic efficiency was 72%.
[0058] Comparative Example 2
[0059] The preparation method of low-cost and high-stability silicon-carbon negative electrode material is the same as that of Example 1, except that in step 2, 15 ml of 0.5 mol / L nitric acid solution is first added, and then 4 ml of 0.5 mol / L hydrofluoric acid solution is gradually added dropwise.
[0060] The obtained low-cost and high-stability silicon-carbon negative electrode material was tested. After 200 cycles of charge and discharge, the capacity of the negative electrode material was 271 mAh / g and the coulombic efficiency was 57%.
[0061] Comparative Example 3
[0062] The method for preparing low-cost and high-stability silicon-carbon negative electrode material is the same as that in Example 1, except that carbon nanotubes are not added in step three.
[0063] The obtained low-cost and high-stability silicon-carbon negative electrode material was tested. After 200 cycles of charge and discharge, the capacity of the negative electrode material was 124 mAh / g and the coulombic efficiency was 35%.
[0064] This solution uses waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystals or solar-grade silicon multi-crystals as raw material to prepare high-performance lithium-ion battery negative electrode materials, which can solve the defect of pure silicon being non-conductive, and realize waste utilization, greatly saving costs.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The steps include: S1. Remove impurities from waste silicon produced by wire cutting during the production of semiconductor-grade silicon single wafers or solar-grade silicon multi-wafers; S2, treating the silicon waste after removing impurities to obtain porous nano-silicon material; S3. Reacting the obtained porous nano-silicon material with a carbon source to obtain a silicon-carbon composite material anchored on the carbon surface.
2. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The specific method of S1 is: using acetone and hydrochloric acid solution to stir and clean the waste silicon generated by wire cutting during the production of semiconductor-grade silicon single crystal wafers or solar-grade silicon multi-crystal wafers to remove impurities.
3. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The specific method of S2 is: using hydrofluoric acid and nitric acid solution to corrode the silicon waste after removing impurities to obtain porous nano-silicon material.
4. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The specific method of S3 is: using magnesium thermal reaction to react the obtained porous nano-silicon material with a carbon source to obtain a silicon-carbon composite material anchored on the carbon surface.
5. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The semiconductor-grade silicon single crystal wafer or the solar-grade silicon multi-crystalline wafer is conductive, and the silicon content in the silicon waste is ≥95%.
6. The method for preparing a silicon-carbon negative electrode material according to claim 2, characterized in that: The molar ratio of acetone and hydrochloric acid solution in S1 is 1:1-2, the liquid-to-solid ratio is 10-15 mL:1 g, and the stirring time is ≥30 min.
7. The method for preparing a silicon-carbon negative electrode material according to claim 3, characterized in that: The hydrofluoric acid solution in S2 is ≥1 mol / L, and the nitric acid solution is ≥0.5 mol / L. The order of adding is to first add the hydrofluoric acid solution, and then gradually drop the nitric acid solution. The molar ratio of nitric acid to hydrofluoric acid solution is 1:1-5.
8. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The corrosion treatment in S2 refers to continuous stirring to make the nanoporous silicon particles become hydrophobic bubbles floating on the surface of the solution. The experiment is stopped when the silicon turns brown and no bubbles are generated. The precipitate containing porous silicon is collected and washed and dried to obtain a porous silicon negative electrode material.
9. The method for preparing a silicon-carbon negative electrode material according to claim 4, characterized in that: In the magnesium thermal reaction in S3, the mass ratio of magnesium powder, porous silicon material and carbon source is 1:1~2:2~5, the heat treatment temperature is 700~900℃, the heating rate is 5℃min-1, and the insulation time is 2~7h.
10. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The carbon source in S3 is carbon nanotubes, graphene or dicyandiamide.
Citation Information
Patent Citations
Preparation method and application of lithium ion battery negative electrode material based on silicon waste of photovoltaic industry
CN104112850A
Preparation method of low-cost nanoporous silicon-carbon composite particles for energy storage
CN106025205A
Method for preparing silicon / carbon composite material with magnesiothermic reduction process
CN106374088A
Honeycomb silicon and carbon composite material and preparation method and application thereof
CN108023076A
Preparation method of silicon carbon-carbon nanotube composite micro-bead anode material for lithium ion batteries
CN110137466A